2007
DOI: 10.1007/s11661-006-9025-1
|View full text |Cite
|
Sign up to set email alerts
|

Liquation Microfissuring in the Weld Heat-Affected Zone of an Overaged Precipitation-Hardened Nickel-Base Superalloy

Abstract: The effect of preweld overaging heat treatment on the microstructural response in the heataffected zone (HAZ) of a precipitation-hardened nickel-base superalloy INCONEL 738LC subjected to the welding thermal cycle (i.e., rapid) was investigated. The overaging heat treatment resulted in the formation of an interfacial microconstituent containing M 23 X 6 particles and coarsening of primary and secondary c¢ precipitates. The HAZ microstructures around welds in the overaged alloy were simulated using the Gleeble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 35 publications
(33 reference statements)
1
29
0
Order By: Relevance
“…This may occur at temperatures below that at which constitutional liquation of c¢ could occur. Ojo et al [18] reported by Gleeble thermal simulation that significant liquation occurs at temperatures below c¢ liquation temperature in the UMT condition. This may be related to liquation reaction of the M 5 B 3 particles that form along grain boundaries during the UMT preweld heat treatment.…”
Section: Improved Preweld Heat Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This may occur at temperatures below that at which constitutional liquation of c¢ could occur. Ojo et al [18] reported by Gleeble thermal simulation that significant liquation occurs at temperatures below c¢ liquation temperature in the UMT condition. This may be related to liquation reaction of the M 5 B 3 particles that form along grain boundaries during the UMT preweld heat treatment.…”
Section: Improved Preweld Heat Treatmentmentioning
confidence: 99%
“…Liquation of c¢ is caused by incomplete dissolution of c¢ particles before the c-c¢ eutectic reaction temperature is reached in the HAZ during the heating cycle of welding. [18] A deviation from the equilibrium precipitate dissolution mechanism occurs during rapid heating such as that experienced during welding. Soucail et al [19] have shown that the solvus temperature of c¢ particles may markedly depart from its equilibrium value during rapid heating, causing these precipitates to survive to significantly higher temperatures than those predicted by the equilibrium phase diagram.…”
Section: Reduced Grain Boundary Liquation and Haz Crackingmentioning
confidence: 99%
See 1 more Smart Citation
“…The test is based on the premise that the deformation behavior of a material, as evaluated by its hot ductility, reflects its capability to accommodate tensile stresses and resist cracking during the welding thermal cycle [21]. The test results indicate that the serrated sample shows a lower susceptibility to liquation cracking than the unserrated one: the GB serration leads to about 15°C decrease in the brittle temperature range (BTR) where HAZ liquation cracking is most likely to occur.…”
Section: Effect Of Gb Serration On Haz Liquation Cracking Behaviormentioning
confidence: 99%
“…The inferiority of WZ of some superalloy materials are originated from brittleclose-packed (TCP) phases as investigated by some researches. 2,3,[7][8][9][10] Fabrication and repair of shroud are performed using conventional Tungsten inert gas (TIG) welding. Nevertheless, the high heat input generates a huge effect on the HAZ resulting in the grain growth and melting of eutectic constituents.…”
Section: Introductionmentioning
confidence: 99%